Performance Test Hammer Mill With Corn Feed Corncob - Octa Rahmadian; Sugeng Triyono; Warji Warji (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2012)
Corn cob is one abundant agricultural waste and potentially viable for animal feed.  Objective of this research was to test a hammer mill to crush the corn cob.  The study was made in two different rotational speeds, 800 rpm and 1400 rpm. A perforated screen (underneath the rotating hammer drum) with 1 cm hole size was used.  The test was conducted in three replications and each replication used 5 kg corn cob.  Variables observed included uniformity of grain sizes of the product and machine capacity.  The expected grain sizes ranged 3 to 7 mm.  The results showed that this machine performed better under 1400 rpm than under 800 rpm.  With 1400 rpm, the machine produced the expected grain sizes of the product about 45,57% by weight, and had a capacity about 15,62 kg/hour. Keywords: Corn cob, Hammer mill, Capacity, Energi consumtion.